2003
DOI: 10.1037/0278-6133.22.3.245
|View full text |Cite
|
Sign up to set email alerts
|

A population study of low-rate smokers: Quitting history and instability over time.

Abstract: This study used one longitudinal and two cross-sectional population surveys to compare stability of low-rate daily smokers (<5 CPD) with other daily smokers and occasional smokers. Most low-rate smokers do not maintain consumption level for long; 36% retained their smoking status after 20 months compared to 82% and 44% for regular daily and occasional smokers, respectively. Analysis revealed a dynamic process; established smokers of all consumption levels quit smoking as well as modified (decreased or increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
79
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 28 publications
10
79
0
1
Order By: Relevance
“…Using a longitudinal population survey, Zhu et al (2003) observed that the majority of light smokers (defi ned as intermittent or daily and smoking less than 5 CPD) identifi ed in California in the early 1990s did not maintain a stable consumption level over a 20-month period. The changes in consumption observed in these longitudinal data could be represented by a dynamic model of quitting and relapse, in which heavier smokers reduced smoking prior to making a quit attempt ( Farkas, 1999 ) and relapse among former smokers began with a period of light smoking.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a longitudinal population survey, Zhu et al (2003) observed that the majority of light smokers (defi ned as intermittent or daily and smoking less than 5 CPD) identifi ed in California in the early 1990s did not maintain a stable consumption level over a 20-month period. The changes in consumption observed in these longitudinal data could be represented by a dynamic model of quitting and relapse, in which heavier smokers reduced smoking prior to making a quit attempt ( Farkas, 1999 ) and relapse among former smokers began with a period of light smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Although cigarette consumption levels below 5 cigarettes/day (CPD) have been labeled as insuffi cient for nicotine regulation and physiological dependence ( Benowitz, Jacob, Kozlowski, & Yu, 1986 ), some smokers may maintain stable behavior at these low levels because of psychological dependence. Alternatively, for heavier smokers, a period of light or intermittent smoking may be part of a dynamic process of attempting to quit ( Zhu, Sun, Hawkins, Pierce, & Cummins, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variation is in how nondaily smoking is defi ned: specifi cally, whether a defi nition is descriptive but imprecise ( " nondaily, " " some-day use, " " occasional, " " occasional but not regularly " ); whether a minimum is specifi ed for lifetime consumption (e.g., at least 100 cigarettes or 100 times); or whether the defi nition is based on cigarettes smoked per day, average number of cigarettes smoked per day, or days or times smoked in a week or a month ( Biener & Albers, 2004 ;Borland, 1994 ;DiFranza et al, 2000 ;Etter, 2004 ;Etter, Le Houezec, & Perneger, 2003 ;Evans et al, 1992 ;Fergusson & Horwood, 1995 ;Fornai et al, 2001 ;Gilpin et al, 1997 ;Hennrikus, Jeffery, & Lando, 1996 ;Hines, Fretz, & Nollen, 1998 ;Hines, Nollen, & Fretz, 1996 ;Holmen, Barrett-Connor, Holmen, & Bjermer, 2000 ;Kenford et al, 2005 ;Koontz et al, 2004 ;Luoto, Uutela, & Puska, 2000 ;McDermott, Dobson, & Owen, 2007 ;Morley et al, 2006 ;Okuyemi et al, 2004 ;Okuyemi, Richter, et al, 2002 ;Paavola, Vartiainen, & Puska, 2001 ;Sargent, Mott, & Stevens, 1998 ;Stanton et al, 2007 ;Stone & Kristeller, 1992 ;Wetter et al, 2004 ;Zhu et al, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…Low-level daily or low-rate daily also has a range of defi nitions from fewer than 5 CPD or no more than 5 CPD ( Kenford et al, 2005 ;Zhu, Sun, Hawkins, Pierce, & Cummins, 2003 ) to, collectively, the group averaging fewer than 10 CPD ( Zvolensky et al, 2007 ). Low-rate smoker is defi ned more consistently as no more than 5 CPD or 1 -5 CPD ( Etter, 2004 ;Owen, Kent, Wakefi eld, & Roberts, 1995 ), but low-level smoker or low-level use has more varied defi nitions ranging from nondaily or no more than 1 pack per week to 1 -20 CPD ( Arcavi, Jacob, Hellerstein, & Benowitz, 1994 ;Dierker et al, 2007 ;Hatsukami et al, 2006 ;Hyland, Rezaishiraz, Bauer, Giovino, & Cummings, 2005 ;Mucha, Stephenson, Morandi, & Dirani, 2006 ).…”
Section: Introductionmentioning
confidence: 99%